The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.aju.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic neo-glans reconstruction after penis-sparing surgery for benign, premalignant or malignant penile lesions

Abstract: PurposeTo describe the technique and results of penis-sparing surgery combined with a cosmetic neo-glans reconstruction for benign, pre-malignant or malignant penile lesions.Patients and methodsTwenty-one patients (mean age 61 years) with penile lesions with a broad spectrum of histopathology underwent organ-sparing surgery with neo-glans reconstruction, using a free split-thickness skin graft harvested from the thigh. Three patients were treated by glans-skinning and glans-resurfacing, 10 by glansectomy and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…Glans resurfacing is indicated in severe LS 47 ; it involves a circumcision and the removal of the penile glandular epithelium. A free split-thickness skin graft then can be harvested from the thigh and transplanted over the glans while using interrupted sutures throughout 48 . Palminteri et al…”
Section: Type Of Urethroplasty Indications Details Of Technique Resultsmentioning
confidence: 99%
“…Glans resurfacing is indicated in severe LS 47 ; it involves a circumcision and the removal of the penile glandular epithelium. A free split-thickness skin graft then can be harvested from the thigh and transplanted over the glans while using interrupted sutures throughout 48 . Palminteri et al…”
Section: Type Of Urethroplasty Indications Details Of Technique Resultsmentioning
confidence: 99%
“…10,13,,20,24,29-30 Their major advantage arises with their ability to minimize cosmetic, sexual and functional drawbacks that characterized the more radical approaches (total or partial penectomy). [3][4]10,24,30 A referral center specializing in the management of benign, premalignant and malignant penile lesions should provide patients with a spectrum of treatment options, dependent upon patient and clinical variables. Whilst data regarding surgical outcomes of the different organ sparing techniques are limited, the evidence is even more sparce for functional outcomes and patient satisfaction, following penile preservation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…6 Some authors have reported satisfactory and excellent TGR outcomes from a functional and sexual point of view, without however having applied any validated scoring tools. [3][4][5]30 Several studies have evaluated patient erectile function via the administration of validated questionnaire (IIEF-5) and/or open questions regarding penile sensation and orgasmic function. 2,[6][7] Hadway et al 2 and O'Kelly 7 reported a IIEF-5 postoperative median score of 24 and 22, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations